Christological paradigm shifts in prophetic Pentecostalism in South Africa - Kgatle, Mookgo S.; Nel, Marius; Banda, Collium (Abingdon, Oxon ; New York : Routledge, 2022)
"This book explores recent developments in South African Pentecostalism, focusing on new prophetic churches. The chapters engage with a number of paradigm shifts in Christology, identified as complementing Christ, competing with Christ, removing Christ, and replacing Christ. What are the implications of these shifts? Does it mean that believers no longer believe in Christ but in their leaders? Does it shift believers' faith towards materiality than the person of Christ? This volume will be valuable for scholars of African Christianity and in particular those interested in the neo-prophetic movement and Christology in a South African context"--
Keywords: Jesus Christ -- History of doctrines; Pentecostal churches -- South Africa; Pentecostal churches -- Doctrines; Pentecostalism -- South Africa; RELIGION / General